2013
DOI: 10.3390/cancers5031049
|View full text |Cite
|
Sign up to set email alerts
|

Glioblastoma-Initiating Cells: Relationship with Neural Stem Cells and the Micro-Environment

Abstract: Glioblastoma multiforme (GBM, WHO grade IV) is the most common and lethal subtype of primary brain tumor with a median overall survival of 15 months from the time of diagnosis. The presence in GBM of a cancer population displaying neural stem cell (NSC) properties as well as tumor-initiating abilities and resistance to current therapies suggests that these glioblastoma-initiating cells (GICs) play a central role in tumor development and are closely related to NSCs. However, it is nowadays still unclear whether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
68
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 76 publications
(71 citation statements)
references
References 127 publications
(156 reference statements)
1
68
1
1
Order By: Relevance
“…Of note however, we previously observed that the activity of CK2α is modulated in malignant gliomas by the expression of connexin 30, a tumor suppressor encoded by GJB6 (20). We likewise observed here that TNF-α, as well as TGF-β1, which are secreted in the microenvironment of gliomas (21)(22)(23), can induce the activity of CK2α and might thus contribute to its hyperactivity in gliomas. These results corroborate a previous report that the activation of NF-κB in response to TNF-α stimulation depends on CK2 (9).…”
Section: Discussionsupporting
confidence: 52%
“…Of note however, we previously observed that the activity of CK2α is modulated in malignant gliomas by the expression of connexin 30, a tumor suppressor encoded by GJB6 (20). We likewise observed here that TNF-α, as well as TGF-β1, which are secreted in the microenvironment of gliomas (21)(22)(23), can induce the activity of CK2α and might thus contribute to its hyperactivity in gliomas. These results corroborate a previous report that the activation of NF-κB in response to TNF-α stimulation depends on CK2 (9).…”
Section: Discussionsupporting
confidence: 52%
“…23 This "seed-and-soil" relationship has also been adapted to cancer stem cell research as GSCs also rely on specific niches to maintain their stem cell properties and ability to drive tumor growth. [24][25][26] In this line, Piccirillo et al recently showed that GSCs isolated from the human SVZ are specifically resistant to supramaximal chemotherapy doses along with differential patterns of drug response. 6 Together, these findings suggest that the SVZ environment might provide GBM cells with radio/ chemoprotective inputs and could play a determinant role in malignant brain tumor recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Bien que l'expression ectopique du facteur de transcription Gli1 ait été associée à la prolifération et à la transformation de nombreux types cellulaires, nous montrons qu'elle peut être interprétée différemment dans le contexte de l'autorenouvellement des CSN adultes. Alors que la ZSV a été proposée comme l'origine potentielle des glioblastomes -des tumeurs cérébrales parmi les plus létales chez l'adulte -nos résultats révèlent la mise en place probable d'un mécanisme de défense du tissu cérébral dans un contexte favorable à la formation de tumeurs [18]. Enfin, nous ne pouvons …”
Section: Sonic Hedgehog Contrôle Le Devenir Des Csnunclassified